Peningkatan Hasil Belajar IPA dan Bahasa Indonesia Menggunakan Metode Demonstrasi dan Pemberian Tugas Siswa Kelas I SDN 186/VI Lubuk Gaung II - Halimatun Sakdiah (Pendidikan Biologi STKIP YPM Bangko, 2021)
In science, learning students at the study results under 5 students from 70 as many as 12 students and indonesian subjects, students at the study results under 3 students from 70 as many as 12 students.The purpose of this research, and is increased the motivation to study by the use of a also students, improve learning outcomes students through method demonstration, described way turn students through integration. Research on the subjects of science siklus1 avarage students from 69 to 76, increase the value while 2 flattened average have increased from 76 to 81.So, increase who signifikan.